Characteristics of frequent adult emergency department users: A Korean tertiary hospital observational study - Lee, Ji Han (Medicine (Baltimore), 2020)
Emergency department (ED) crowding is a public health burden that impedes the provision of high-quality emergency care and is related to poor outcomes. Frequent ED visits are known to contribute to ED crowding. This study aimed to identify frequent ED users’ characteristics and risk factors related to frequent ED visits. A retrospective observational study was conducted using ED-based data derived from adult patients at a university hospital. The main exposure variable was frequent ED visits, which were defined as ≥4 visits within 12 months (January 1–December 31, 2018). Characteristics and risk factors for frequent ED users were evaluated using stepwise regression analysis. Within the study period, there were 36,932 ED visits involving 29,759 patients. Of these, 3031 (8.2%) visits were from 556 (1.9%) patients classified as frequent ED users. The independent risk factors for frequent ED visits were older patients (≥65 years); the winter season; daytime discharge from ED; patients with medical aid insurance; and patients designated as high acuity at their first visit. Patients with a malignant neoplasm, mental health disorder, alcohol-related liver disease, chronic kidney disease, or chronic obstructive pulmonary disease were associated with more frequent ED visits. Frequent ED users comprised a significant proportion of total ED visits. Frequent ED users were more likely than occasional ED users to be in poorer health, older, or have a chronic disease or a mental health disorder.